The basic study of the relation between the safe areas and fan position by using the Particle Image Velocimetry. Issue 3 (March 2020) - Hong, Liu
Abstract: Nowadays, the safety of large areas has become the focus of attention. The gas leak will easily cause the terrible losses of lives and property if the appropriate measures are not taken immediately. Therefore, once the similar situation happens, the toxic gas must be dealt with timely to adjust the safe areas of the large space and ensure the necessary security of people. On the basis of the background, this paper introduces a method to study the relationship between the safe areas and the fan position by using the PIV (Particle Image Velocimetry).